Legal reflections on the constitutional and criminal recognition of indigenous law - Santacruz Cruz, Santacruz Cruz (2020)
In Latin American countries, the idea of legal pluralism and the beginning of processes aimed at the search for normative decolonization have shown a slow evolution. Much of this slow development has been due to the monopolization of the administration of justice by the State, given that state intervention has resulted in the criminalization of the forms of social control of indigenous peoples that were once allowed. However, in recent times the constitutional recognition of indigenous justice has allowed indigenous peoples to recreate and apply their own forms of social control regarding behaviors that the community considers unapproved. State interference is reluctant to give up its interventionism and for that purpose it uses infra-constitutional legislation that has not presented the same constitutional development, since in these persistence the inferiority lags were believed to have been overcome. In this sense, this article intends to present, on the one hand, a descriptive vision of the rights recognized by the constitutions of the countries that make up the Community of Andean Nations and on the other, the lack of harmony that exists with respect to current legislation, not only limiting but criminalizing the administration of indigenous justice.